Mirror symmetry and the classification of orbifold del Pezzo surfaces - Akhtar, Mohammad; Coates, Tom; Corti, Alessio; Heuberger, Liana; Kasprzyk, Alexander M.; Oneto, Alessandro; Petracci, Andrea; Prince, Thomas; Tveiten, Ketil (American Mathematical Society, 2016)
We state a number of conjectures that together allow one to classify a broad class of del Pezzo surfaces with cyclic quotient singularities using mirror symmetry. We prove our conjectures in the simplest cases. The conjectures relate mutation-equivalence classes of Fano polygons with Q-Gorenstein deformation classes of del Pezzo surfaces.